Analysis of Firm Value Determination on the IDX Sharia Growth Index - Tri Purwani; Rahmat Budi Santoso (International Business and Accounting Research Journal, 2023)
This study aims to examine the effects of profitability, net profit growth, company liquidity, company size, company growth, capital structure, and dividend policy on the value of the firms listed on the index of IDX Sharia Growth at the Indonesian Stock Exchange. The samples used were 64 samples. The results of this study showed that profitability, net profit growth, company liquidity, company size, capital structure and dividend policy have a significant positive effect on firm value, while company growth has no effect on firm value. Profitability has the greatest effect in influencing the firm value. The results of the study concluded that investors pay more attention to company profitability than other factors in buying company shares. Thus, companies need to maximize the profits to attract investors, so that the stock price and firm value will increase.